Repertoire Sequencing of B Cells Elucidates the Role of UNG and Mismatch Repair Proteins in Somatic Hypermutation in Humans - IJspeert, Hanna; van Schouwenburg, Pauline A.; Pico-Knijnenburg, Ingrid; Loeffen, Jan; Brugieres, Laurence; Driessen, Gertjan J.; Blattmann, Claudia; Suerink, Manon; Januszkiewicz-Lewandowska, Danuta; Azizi, Amedeo A.; Seidel, Marcus G.; Jacobs, Heinz; et al. (Frontiers in Immunology, 2019)
The generation of high affinity antibodies depends on somatic hypermutation (SHM). SHM is initiated by the activation induced cytosine deaminase (AID) which generates uracil (U) lesions in the B-cell receptor (BCR) encoding genes. Error-prone processing of U lesions creates a typical spectrum of point mutations during SHM. The aim of this study was to determine the molecular mechanism of SHM in humans, since current knowledge on SHM in humans is limited and is predominantly based on mice data. We collected a unique cohort of ten well-defined patients with bi-allelic mutations in genes involved in base excision repair (UNG), or mismatch repair (MSH2, MSH6, or PMS2) and are the first to present next generation sequencing data of the BCR, allowing us to study SHM extensively in humans. Analysis using ARGalaxy revealed selective skewing of SHM mutation patterns specific for each genetic defect, which are in line with the five pathway model of SHM that was recently proposed based on mice data. However, trans-species comparison revealed differences in the role of PMS2 and MSH2 in strand targeting between mice and man. In conclusion, our results indicate a role for UNG, MSH2, MSH6 and PMS2 in the generation of SHM in humans comparable to their function in mice. However, we observed differences in strand targeting between humans and mice, emphasizing the importance of studying molecular mechanisms in the human setting. The here developed method combining NGS and ARGalaxy analysis of BCR mutation data forms the basis for efficient SHM analyses of other immune deficiencies.